Optimization of The Madani Bintan Islamic Boarding School Aplication in The Implementation of Education Accountability - Nurul Fitriyana Ahmad; Erni Munastiwi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2022)
This study aims to describe the optimization of the application of the Madani Bintan Islamic boarding school in the implementation of educational accountability at Madrasah Aliyah Madani Bintan. The method used in this research is descriptive. The approach taken is a qualitative approach. The data collection tool used in this study consisted of three parts, namely observation, interviews and documentation. Based on the results of the research, it is known that: (1) Through the application, parents can monitor activities, the achievements are inputted by the operator every month to be reported to caregivers and parents. Parents can access the application. Then in the application, the profile of each student is entered and can be accessed by the parents of each student. In this application, parents can monitor their child's achievement. Even to the point of prayer, the offense was committed. (2) the results of interviews with several guardians of students can be concluded that the application of this Islamic boarding school is very useful and helps parents of students to make monthly payments for Islamic boarding schools. In addition, this application can help parents to monitor their children's activities while at the boarding school.